Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa Melalui Inovasi Pembelajaran PAI Berbasis Cooperative Learning - Andis Suha Fadhilah; Sal Shakhiba Albira Nanda Hanafi; Abdul Bashith (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2025)
Critical and creative thinking skills are very important in supporting a meaningful learning process, especially in Islamic Religious Education (PAI). Unfortunately, one-way learning methods are still commonly found that do not encourage students' active involvement. The purpose of this research is to find out how the cooperative learning model can train students' critical and creative thinking skills in Islamic Education subjects, as well as its contribution in creating active, participatory, and meaningful learning in value. This research uses a qualitative approach with a library research method. Data sources were obtained from scientific literatures such as books, journals, articles, previous research results, and other documents relevant to the topic of PAI learning and cooperative learning. This research discusses the use of cooperative learning model as a strategy to improve both abilities. The results show that cooperative learning can encourage students to actively discuss, think analytically, and develop new ideas. Thus, Cooperative Learning can be an innovative alternative in learning PAI that is more interactive and effective.